2019
DOI: 10.3892/or.2019.6963
|View full text |Cite
|
Sign up to set email alerts
|

CTHRC1 overexpression promotes cervical carcinoma progression by activating the Wnt/PCP signaling pathway

Abstract: The tumorigenesis and metastasis of tumors are associated with human collagen triple helix repeats containing 1 (CTHRC1). To study the effects and possible impacting mechanisms of CTHRC1 on human cervical carcinoma development, samples of paraffin-embedded cervical carcinoma and HeLa cells were examined. Immunofluorescence, cell wound scratch assay, western blot analysis and Transwell invasion assay were used to evaluate HeLa cells in response to silencing of the CTHRC1 gene in cervical carcinoma. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…It has been confirmed that CTHRC1 can activate the SRC and ERK signal cascades and upregulate the expression of MMP9, thus promoting the invasion of CRC cells (22). Overexpression of CTHRC1 has been found to promote the occurrence and development of cervical cancer by activating the Wnt/PCP oncogenic signaling pathway (57). CTHRC1 induces EMT changes and MMP expression through the PI3K/AKT/ERK/CREB signaling pathway to promote the invasiveness and metastasis of hepatocellular carcinoma (58).…”
Section: Discussionmentioning
confidence: 91%
“…It has been confirmed that CTHRC1 can activate the SRC and ERK signal cascades and upregulate the expression of MMP9, thus promoting the invasion of CRC cells (22). Overexpression of CTHRC1 has been found to promote the occurrence and development of cervical cancer by activating the Wnt/PCP oncogenic signaling pathway (57). CTHRC1 induces EMT changes and MMP expression through the PI3K/AKT/ERK/CREB signaling pathway to promote the invasiveness and metastasis of hepatocellular carcinoma (58).…”
Section: Discussionmentioning
confidence: 91%
“…Among those predicted signaling pathways, the PCP signaling axis was the top pathway judged by significant p value and activation status (activation z-score = 3.162, Figure 4 A). PCP signaling is one of the noncanonical Wnt signaling pathways of whose aberrant activation could lead to tumor migratory properties [ 15 , 16 , 17 , 18 ]. The distribution of up- and downregulated gene targets is shown in Figure 4 B.…”
Section: Resultsmentioning
confidence: 99%
“…CTHRC1 played a role in the cellular response to arterial injury through involvement in vascular remodeling (Pyagay et al, 2005). Previous studies showed that CTHRC1 promoted tumor cell progression and might play a key role in the invasion metastasis of cervical carcinoma, cervical squamous cell carcinoma, and colorectal cancer (Ni et al, 2018;Li N. et al, 2019;Zheng et al, 2019). In addition, CTHRC1 promoted M2-like macrophage recruitment and myometrial invasion in endometrial carcinoma by the integrin-Akt signaling pathway, which indicated that CTHRC1 might be a biomarker for tumor immunotherapy .…”
Section: Discussionmentioning
confidence: 99%